Designing Several Types of Oscillation-Less and High-Resolution Hybrid Schemes on Block-Structured Grids (Communications in Computational Physics, 2018)
An idea of designing oscillation-less and high-resolution hybrid schemes isproposed and several types of hybrid schemes based on this idea are presented onblock-structured grids. The general framework, for designing various types of hybridschemes, is established using a Multi-dimensional Optimal Order Detection (MOOD)method proposed by Clain, Diot and Loubère [1]. The methodology utilizes low dissipationor dispersion but less robust schemes to update the solution and then implementsrobust and high resolution schemes to deal with problematic situations. Awide range of computational methods including central scheme, MUSCL scheme, linearupwind scheme and Weighted Essentially Non Oscillatory (WENO) scheme havebeen applied in the current hybrid schemes framework. Detailed numerical studieson classical test cases for the Euler system are performed, addressing the issues of theresolution and non-oscillatory property around the discontinuities.